Skeletal Muscle and Bone – Emerging Targets of Fibroblast Growth Factor-21 - Sun, Hui; Sherrier, Matthew; Li, Hongshuai (Frontiers in Physiology, 2021)
Fibroblast growth factor 21 (FGF21) is an atypical member of the FGF family, which functions as a powerful endocrine and paracrine regulator of glucose and lipid metabolism. In addition to liver and adipose tissue, recent studies have shown that FGF21 can also be produced in skeletal muscle. As the most abundant tissue in the human body, skeletal muscle has become increasingly recognized as a major site of metabolic activity and an important modulator of systemic metabolic homeostasis. The function and mechanism of action of muscle-derived FGF21 have recently gained attention due to the findings of considerably increased expression and secretion of FGF21 from skeletal muscle under certain pathological conditions. Recent reports regarding the ectopic expression of FGF21 from skeletal muscle and its potential effects on the musculoskeletal system unfolds a new chapter in the story of FGF21. In this review, we summarize the current knowledge base of muscle-derived FGF21 and the possible functions of FGF21 on homeostasis of the musculoskeletal system with a focus on skeletal muscle and bone.